2001
DOI: 10.1007/s11661-001-1023-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-tempering analysis of bulk metallic glass plates using an instant-freezing model

Abstract: The viscoelastic nature of bulk metallic glasses (BMGs), their low thermal conductivity, and the fast cooling used in their processing subject them to thermal tempering. This process leads to a residual stress state in which compression on the surface is balanced by tension in the interior. For the first time, we have calculated such stresses in metallic glasses by adapting an analytical instant-freezing model previously developed for silicate glasses. This model has been demonstrated to be reasonably accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…We can now match all experimental data and obtain strong localization in agreement with experimental observations [1]. We have also developed specialized strain-localization finite elements that match experimental data on dynamic shear band propagation [2][3][4].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We can now match all experimental data and obtain strong localization in agreement with experimental observations [1]. We have also developed specialized strain-localization finite elements that match experimental data on dynamic shear band propagation [2][3][4].…”
Section: Discussionmentioning
confidence: 60%
“…Third, elastic modulus and Poisson's ratio differ depending on the cooling rates of samples which indicates that the sound propagation velocities of plane waves (longitudinal and transverse) in the samples are significantly different depending on the different cooling rate during processing. Binary BMG Alloys It has been proposed as an empirical rule that in order to form a bulk amorphous structure a metallic system must comprise at least three elements [1]. Nevertheless, in an attempt to establish a good starting point for new rnulti-component bulk metallic glasses, several binary alloys were found to form bulk amorphous structures by themselves using the regular copper mold casting method, although they only consist of two elements.…”
Section: Ni-based Alloysmentioning
confidence: 99%
“…Its variation was more pronounced (about 3%) for the "Elastic SS" case. This insensitivity is attributed to the saturation of the temper level at these high values of heat transfer coefficient [3,4].…”
Section: Resultsmentioning
confidence: 99%
“…This is a wellestablished process in silicate glasses [3]. Thermal tempering in BMGs has been recently investigated for the first time by Aydiner et al in a series of systematic studies [4][5][6]. Aydiner et al showed that the thermoviscoelastic model they developed earlier can predict residual stresses within 15-30% of experimental data [6].…”
Section: Introductionmentioning
confidence: 99%
“…[13] As stated earlier, quench stresses are an inevitable outcome of metallic glass production, while thermal tempering is regularly used to introduce a beneficial residual stress profile (compressive surface residual stresses balanced by the midplane tension) into silicate glasses [14] and BMGs. [15,16] Favorable compressive residual stresses can also be generated by introducing surface plastic deformation, for example, by shot peening (bombarding the surface with small ''shot''). This surface engineering process can enhance the ductility of BMGs, depending on the load case.…”
Section: Introductionmentioning
confidence: 99%